Some issues in system identification using clustering - Nikhil, R.; Kuhu Pal; Bezdek, J.C.; Runkler, T.A. (1997 IEEE International Conference on Neural Networks, 1997)
This article surveys the use of clustering for identification of various parameters of fuzzy systems. Issues discussed include the proper domain for clustering, the clustering algorithm used, validation of clusters, and system validation.